KAZNET Web Application User Guide - Lepariyo, Watson; Shikuku, Kelvin Mashisia; Alulu, Vincent; Baraza, Meshack; Galgallo, Diba; Gobu, Wako; Godana, Nura; Banerjee, Rupsha R. (International Livestock Research Institute, 2025)
KAZNET was designed to use citizen science and crowdsourcing techniques to monitor shocks and resilience indicators at markets, rangelands, and household level and to disseminate this information near-real-time to end users for decision support and as a de-risking measure. KAZNET is based on a mobile and web-based application designed for seamless data collection and management. It enables “contributors” to collect field data through assigned tasks and information users to access information. The system supports offline data collection, ensuring flexibility in various field conditions, and provides a structured approval workflow to maintain data accuracy and integrity. With real-time synchronization, KAZNET ensures efficient and secure data management for informed decision-making.